2018
DOI: 10.20344/amp.9090
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia Rapid Test: Estudos de Tradução, Adaptação e Validação para a População Portuguesa

Abstract: RESUMOIntrodução: As baterias clássicas de caracterização de afasia são demasiado longas para serem utilizadas no contexto do acidente vascular cerebral agudo ou como ferramenta de monitorização. O Aphasia Rapid Test é uma escala de 26 pontos desenvolvida como teste de cabeceira para avaliar a gravidade da afasia num doente com acidente vascular cerebral em menos de três minutos. O objetivo do estudo é adaptar e validar a escala para o português europeu. ABSTRACT Introduction: Classical aphasia evaluation scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…This finding is in line with the French study of Azuar et al with a coefficient of concordance of 0.990 (rater 1=13.4, rater 2=13.49) [11], and the Italian study of Panebianco et al with a coefficient of concordance of 0.99 (rater 1=9.38, rater 2=9) [13]. Also, the Portuguese study of Tábuas-Pereira et al reported an excellent concordance coefficient (0.985) between rater 1 and rater 2 [14]. The significant interrater reliability found in the current study suggests that different examiners can perform PART without affecting the results.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This finding is in line with the French study of Azuar et al with a coefficient of concordance of 0.990 (rater 1=13.4, rater 2=13.49) [11], and the Italian study of Panebianco et al with a coefficient of concordance of 0.99 (rater 1=9.38, rater 2=9) [13]. Also, the Portuguese study of Tábuas-Pereira et al reported an excellent concordance coefficient (0.985) between rater 1 and rater 2 [14]. The significant interrater reliability found in the current study suggests that different examiners can perform PART without affecting the results.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the present results, they found a high correlation between early results from ART and later results from the Boston Diagnostic Aphasia Examination [11]. Moreover, the Portuguese study showed a high correlation between the ART scores and the Lisbon aphasia examination [14]. The Italian study did not compare the ART scores with other aphasia tests [13].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations